Tingkat Perubahan Suhu di Kota Bengkulu di Lihat dari Intensitas Curah Hujan yang Terjadi dalam Rentang Waktu 6 Tahun (2018-2023) - Keyshe Nur Cholisa; Wira Citra, Fevi; Zahrizal, Debby; Dwi Putri, Sari; Antini, Lusi (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2024)
Sumatra Island is an area with high rainfall throughout the year, Bengkulu City which is located in the coastal area causes the air to be relatively hot with air temperatures throughout the year relatively the same, air temperature is influenced by the topography of an area. Indication of changes in rainfall intensity can be done by analyzing rainfall calculation time data and temperature degrees that can provide factor information and causes of temperature changes. The research method used is quantitative research. The data used are monthly rainfall data and monthly average air temperature within a period of 6 years, in the period from 2018 to 2023 data sources from the Class I Climatology Station of Baai Island Bengkulu. The level of temperature change that occurs in Bengkulu City is not influenced by rainfall alone, but is also influenced by factors such as wind patterns, air pressure, climate, regional topography and sea level heat rise in Bengkulu City.